2019
DOI: 10.1098/rstb.2018.0192
|View full text |Cite
|
Sign up to set email alerts
|

Ant behaviour and brain gene expression of defending hosts depend on the ecological success of the intruding social parasite

Abstract: The geographical mosaic theory of coevolution predicts that species interactions vary between locales. Depending on who leads the coevolutionary arms race, the effectivity of parasite attack or host defence strategies will explain parasite prevalence. Here, we compare behaviour and brain transcriptomes of Temnothorax longispinosus ant workers when defending their nest against an invading social parasite, the slavemaking ant Temnothorax americanus . A full-factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 85 publications
0
37
0
Order By: Relevance
“…Another important learning gene is glutamate receptor ionotropic, NMDA 2B isoform X3 , which was up‐regulated in T. longispinosus scouts compared to followers (Table ). In an earlier study, we already found glutamate receptor NMDA to be up‐regulated in the brain of T. longispinosus workers, at that time in response to an attacking slavemaker (Kaur et al, ). Our findings are in line with previous investigations into honeybees, in which genes related to glutamate signalling were up‐regulated in scouts (Liang et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Another important learning gene is glutamate receptor ionotropic, NMDA 2B isoform X3 , which was up‐regulated in T. longispinosus scouts compared to followers (Table ). In an earlier study, we already found glutamate receptor NMDA to be up‐regulated in the brain of T. longispinosus workers, at that time in response to an attacking slavemaker (Kaur et al, ). Our findings are in line with previous investigations into honeybees, in which genes related to glutamate signalling were up‐regulated in scouts (Liang et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Stoddard et al [56] Yang et al [57] Kaur et al [59] Hanley et al [60] McClelland et al [76] What cognitive rules do hosts use to distinguish kin from non-kin?…”
Section: Resultsmentioning
confidence: 99%
“…Insect hosts of brood parasites, on the other hand, tend to have distinctive cuticular hydrocarbon profiles that can be used to discriminate kin or social partners [92 -95], leading to chemical mimicry [96] or camouflage [97]. Kaur et al [21] measured the aggressive responses displayed by hosts to slavemaking ants across a number of populations. Surprisingly, the best predictor of the host response, both behaviourally and in terms of gene expression in the brain, was the ecological success of the parasite.…”
Section: (Ii) Defending the Body/nestmentioning
confidence: 99%
“…In the most extreme cases, hosts can even abandon a nest that is heavily infected with parasites, as has been shown in ants [38] and termites [39], thus killing the parasite by depriving it of hosts. Similarly, brood parasite hosts can also show resistance by ejecting the parasite from the nest [98] or directly killing it [21]. There is also evidence that some hosts will abandon infected nests after brood parasites have been detected.…”
Section: (Ii) Defending the Body/nestmentioning
confidence: 99%
See 1 more Smart Citation